2002
DOI: 10.1364/ol.27.001643
|View full text |Cite
|
Sign up to set email alerts
|

Integrated fiber Mach–Zehnder interferometer for electro-optic switching

Abstract: Molten alloys under high pressure were used to obtain fibers with long internal electrodes that are solid at room temperature. An integrated Mach-Zehnder interferometer was constructed from a twin-core twin-hole fiber that permitted application of an electric field preferentially to one of the cores. Good stability and a switching voltage of 1.4kV were measured with a 1-m-long fiber device with a quadratic voltage dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(66 citation statements)
references
References 8 publications
0
62
0
4
Order By: Relevance
“…For our initial induction poling experiments, we used a pressure filling technique similar to the one described by Fokine et al [3] to fill the internal holes with BiSn eutectic alloy as shown in Fig. 1 (left).…”
Section: Methodsmentioning
confidence: 99%
“…For our initial induction poling experiments, we used a pressure filling technique similar to the one described by Fokine et al [3] to fill the internal holes with BiSn eutectic alloy as shown in Fig. 1 (left).…”
Section: Methodsmentioning
confidence: 99%
“…The electrode liquids used to fill the twin-hole fiber samples were Gallium, Mercury, 20% HCl solution and ordinary tap water. The liquid metals were introduced into the samples using pressurization techniques [5] whereas the aqueous solutions could be inserted via normal capillary action. After filling, tungsten wires are inserted into the twin holes at one end of the samples, ensuring electrical contact with the liquid.…”
Section: Silica Fiber Thermal Poling Using Novel Liquid Electrode Typesmentioning
confidence: 99%
“…In addition they are examined for evidence of depletion region formation and for the development of second-order nonlinearities as evaluated by quasi-phase matching (QPM) at a particular pump wavelength, by measuring the generated second harmonic generated (SHG) power. Comparing electrode materials can identify new routes towards the realization of long, robust, low loss, highly efficient nonlinear all-fiber devices for use in, for example, frequency conversion [3], electro-optic modulation and switching [5] and polarization entangled photon pair generation.…”
Section: Introductionmentioning
confidence: 99%
“…The sample is a twin-hole Germania doped fused silica fiber (length ≈ 20 cm, OD = 125 µm). The two holes of the sample were fully filled with metallic liquid electrodes by means of a pressure filling technique similar to the one described in [10]. The experimental setup of an induction poling experiment is reported in Fig.1.…”
Section: Geometry Of the Modelmentioning
confidence: 99%